Dual-sensitive chitosan derivative micelles for site-specific drug release in the treatment of chicken coccidiosis. Issue 26 (17th April 2018) - Zhang, Xin; Xu, Gujun; Gadora, Khalid; Cheng, Hao; Peng, Jin; Ma, Yong; Guo, Yang; Chi, Cheng; Zhou, Jianping; Ding, Yang
Abstract : Here, we report a "dual-sensitive" drug delivery platform packaged with anti-coccidia drug diclazuril (DIC) applied in the field of intestinal-targeted administration. Abstract : Coccidiosis is a widespread and economic disease that deteriorates the growth of infected animals and largely affects our food safety. It has been proved that chitosan and its derivatives could offer outstanding antibacterial and hemostatic capabilities and help increase weight gain in the breeding of poultry. Herein, we put forward a novel strategy for the development of anti-coccidiosis drug formulations, aiming to synthesize 3-carboxyphenylboronic acid (CPBA) modified chitosan (CS) conjugates which could be self-assembled into polymeric micelles together with diclazuril (DIC), a poorly water-soluble coccidiostat drug, for site-specific drug release in the treatment of animal coccidiosis. The CPBA-modified micelles possessed specific glucose and pH dual-responsive capacity. The cumulative release of DIC reached the maximum of 85.0% at pH 6.8 and 50 mM glucose, while only 44.2% at pH 2.0 and no glucose, which allows drug to be released in the intestinal tract with neutral pH and glucose existence. 1 H NMR and FTIR confirmed the successful synthesis of amphiphilic polymer; and the optimized DIC-loaded CS–CPBA micelles (DIC/CS–CPBA) shared nanoscale particle size of (118.9 ± 1.1) nm, drug loading of 8.97% and spherical shape. The pharmacokinetic results indicated that the AUC value of DIC/CS–CPBA micelles was 1.7 times than that of drug suspensions. The anti-coccidial efficacy demonstrated that DIC/CS–CPBA micelles improved the anticoccidial efficacy in vivo and reduced intestinal damage. These results indicated that phenylboronic acid-conjugated chitosan micelles provided a promising platform for specific-targeted drug release in the intestinal tract for the treatment of coccidiosis.